Developing a Measure of Interpersonality - Mesa, Rica Faith Creencia; Alaron, Angel Licel Rose Adto; Cadavedo, Jamaica Manzano; Calabio, April Octa; Costa, Mark Aldrin Esguerra; Mendoza, Franceska Nicole Abinales; Panganiban, Aila Castro; Hilario, Paulito (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2024)
This study aimed to develop a scale that measures a construct of Filipino Psychology, which is pakikipagkapwa-tao, a key construct in Filipino Psychology grounded in Enriquez’s